Biological consequences of structural and functional proteasome diversity - Alexey V. Morozov; Vadim L. Karpov (Heliyon, 2018)
Cell homeostasis and regulation of metabolic pathways are ensured by synthesis, proper folding and efficient degradation of a vast amount of proteins. Ubiquitin-proteasome system (UPS) degrades most intracellular proteins and thus, participates in regulation of cellular metabolism. Within the UPS, proteasomes are the elements that perform substrate cleavage. However, the proteasomes in the organism are diverse. Structurally different proteasomes are present not only in different types of cells, but also in a single cell. The reason for proteasome heterogeneity is not fully understood. This review briefly encompasses mammalian proteasome structure and function, and discusses biological relevance of proteasome diversity for a range of important cellular functions including internal and external signaling.